Touch as part of parent-child communication with a child mechanically ventilated at home – introduction to the issue - Kamyk-Wawryszuk, Agnieszka (Specijalna edukacija i rehabilitacija, 2025)
A mechanically ventilated child, due to frequent hospitalizations and associated participation in sometimes painful medical procedures, may associate touch negatively. The article’s purpose is to show the place of touch in communication between a parent and a child who is mechanically ventilated at home. It indicates the importance of touch and its role when a child requires medical equipment for everyday functioning and does not use verbal language to communicate with others.  Such an experience – a negative touch associated with an adult - can also be transferred to relationships with other people and be used in communication. It can contain elements of aggression and resistance based on the child’s fear of contact. The child’s stay at home will be associated with learning to communicate based on positive touch. It is possible that signals can be introduced to anticipate the activity in which the child will participate. This process will build a sense of security in them, reduce their fear of contact with an adult, and give them a sense of agency.
Keywords: touch; parent; mechanically ventilated child (LTV)